2022
DOI: 10.1371/journal.pone.0268119
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on COVID-19 infections and mortality in Germany: Insights from age- and gender-specific modeling of contact rates, infections, and deaths in the early phase of the pandemic

Abstract: Recent research points towards age- and gender-specific transmission of COVID-19 infections and their outcomes. The effect of gender, however, has been overlooked in past modelling approaches of COVID-19 infections. The aim of our study is to explore how gender-specific contact behavior affects gender-specific COVID-19 infections and deaths. We consider a compartment model to establish short-term forecasts of the COVID-19 epidemic over a time period of 75 days. Compartments are subdivided into different age gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 42 publications
10
52
5
3
Order By: Relevance
“…This result in our study is consistent with many studies, including the study of Guido Iaccarino and his colleagues in Italy [5] As for age, our study agreed with the consensus of international studies on the increased risk and rates of infection and access to care for the elderly, including the study of Achim Doerre and his colleagues in Germany. [6] As for the radiological ndings, the pulmonary consolidation were the most common nding in our study, we found a difference in other studies that found that the most common ndings were the ground glass opacities and the consolidation together, such as the Chinese study of Ming-Yen and his colleagues , [7] and this can be attributed to a difference in the timing of taking the radiological ndings or the classi cation method.…”
Section: Discussioncontrasting
confidence: 71%
“…This result in our study is consistent with many studies, including the study of Guido Iaccarino and his colleagues in Italy [5] As for age, our study agreed with the consensus of international studies on the increased risk and rates of infection and access to care for the elderly, including the study of Achim Doerre and his colleagues in Germany. [6] As for the radiological ndings, the pulmonary consolidation were the most common nding in our study, we found a difference in other studies that found that the most common ndings were the ground glass opacities and the consolidation together, such as the Chinese study of Ming-Yen and his colleagues , [7] and this can be attributed to a difference in the timing of taking the radiological ndings or the classi cation method.…”
Section: Discussioncontrasting
confidence: 71%
“…This result in our study is consistent with many studies, including the study of Guido Iaccarino and his colleagues in Italy [5] As for age, our study agreed with the consensus of international studies on the increased risk and rates of infection and access to care for the elderly, including the study of Achim Doerre and his colleagues in Germany. [6] As for the radiological ndings, the pulmonary consolidation were the most common nding in our study, we found a difference in other studies that found that the most common ndings were the ground glass opacities and the consolidation together, such as the Chinese study of Ming-Yen and his colleagues , [7] and this can be attributed to a difference in the timing of taking the radiological ndings or the classi cation method.…”
Section: Discussioncontrasting
confidence: 68%
“…Indeed, females and those with a lower educational level had a higher concern of side effects of the vaccination and this reflects the general trend in access to COVID-19 vaccine disparities that has been observed in several previous studies ( 33 37 ). The reason by which females are more concerned may be explained by the fact that in Italy they were more affected than men although male presented a higher risk of death ( 38 ). With regard to the results of the educational level, a possible explanation is that parents with a higher level are able to get more information easier than the general population that makes them advantageous over part of the other societies.…”
Section: Discussionmentioning
confidence: 99%